PENGARUH KUALITAS PELAYANAN PEWARNAAN RAMBUT TERHADAP KEPUASAN KONSUMEN DI MINI SALON SURABAYA - Nadia Agnissia Putri; Biyan Yesi Wilujeng; Octaverina Kecvara Pritasari; Novia Restu Windayani (Jurnal Tata Rias, 2026)
This study aims to determine the compliance of hair coloring services at Mini Salon Surabaya with the Indonesian National Work Competency Standards (SKKNI), analyze the effect of hair coloring service quality on customer satisfaction, and determine the level of customer satisfaction with the service. This study used a quantitative approach with simple linear regression. The population was consumers who had their hair colored at Mini Salon Surabaya. Data collection techniques included observation and a Likert-scale questionnaire. The results indicate that the Standard Operating Procedure (SOP) for hair coloring at Mini Salon Surabaya complies with the 2021 SKKNI, covering the preparation phase, the coloring process, and the end of the service. Based on the results of simple linear regression analysis and hypothesis testing (t-test), hair coloring service quality has a positive and significant effect on customer satisfaction. This indicates that the better the service quality, the higher the level of customer satisfaction. The coefficient of determination (R²) indicates that service quality contributes to customer satisfaction, while the remaining influence is due to other factors outside the study.